PERMASALAHAN DAN USAHA KONSERVASI ANOA SEBAGAI FAUNA ENDEMIK SULAWESI - Baderan, Dewi Wahyuni K (Sainstek, 2007)
Sulawesi is a priceless island for biology conservation due to the fact that it has high level of endemic. This is not only the proud for Sulawesi, but also the huge responsibility to bear. Sulawesi is supposed to manage it so that it will benefit future life. Yet, the irresponsible deed has ended up in the rapid extinction of flora and fauna in Sulawesi and other islands in Indonesia. Since 1931 the endemic fauna in Sulawesi has been classified into scarce protected fauna. We have no rights to catch, hurt, kill, store, possess, keep, carry, and sell live or dead fauna. Although there have been a lot of activities for preserving the continuity of this wildlife and laws that rule the preservation, but extinction still threatens. Therefore, these laws must be implemented well. Besides, it is necessary to set a sustainable well organized effort that involve government and people in order to keep this wildlife since the variety of flora and fauna is part of our priceless natural resources.